Construction project budgeting including time buffers and costs - Połoński, Mieczysław (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The proposed method presented in this article concerns cost estimating of projects, including contingency. It points to the possibility of application of time buffers for this purpose. From the practical point of view, the enhanced calculation at the planning stage of works, taking into account cost contingency, is important and meets the expectations of owners, who tend to exceed the planned costs of investment without considering reserve costs. The implementation of the calculation is relatively simple, and basically requires one person to be acquainted with the planned costs of particular tasks, even in a deterministic way. This article presents the assumptions of the proposed method and a calculation example involving a real construction object. Depending on the data available to the planner, the results are presented concerning the calculations of the amount of cost contingency of the entire project by way of seven variants of calculation. With reference to the provided example, depending on the applied method, the increase of the cost of the entire undertaking ranges from 21-36 % of the costs of the entire project. The highest contingency costs were obtained by using the risk analysis method (35-36 %). Other methods gave consistent results within the range of 21-26% of the costs of the entire object. In the conclusion, a continuous curve is shown depicting an increase of costs during the planned works.